Digital Education for Self-Care Behavior to Prevent Respiratory Infections in Vulnerable Populations: A Review - Moreal, Chiara; Chiappinotto, Stefania; Dentice, Sara; Palese, Alvisa; Dobrowolska, Beata (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Digital education is increasingly recognised as powerful tool for addressing inequities in healthcare and education among vulnerable populations. Such populations, characterised by specific disadvantages, frequently encounter significant obstacles in accessing conventional educational and healthcare resources. The advent of the global pandemic, namely the Coronavirus disease 2019 (Covid-19), has further compounded the challenges confronting these populations, thereby necessitating the development of novel approaches to address their educational needs. Furthermore, health prevention strategies have been shown to improve general outcomes and protect communities. Digital technologies, including telehealth platforms, mobile health applications, and online learning systems, have emerged as useful solutions to overcome these challenges, offering scalable, flexible, and cost-effective ways to deliver tailored educational content while empowering users to take the respoabnbility to develop and mantein their health and wellbeing.